New Mitochondrial Targets in Fungal Pathogens - Daniel Murante (American Society for Microbiology, 2019)
ABSTRACT In eukaryotic cells, mitochondria are responsible for the synthesis of ATP using power generated by the electron transport chain (ETC). While much of what is known about mitochondria has been gained from a study of a small number of model species, including the yeast Saccharomyces cerevisiae, the general mechanisms of mitochondrial respiration have been recognized as being highly conserved across eukaryotes. Now, Sun et al. (N. Sun, R. S. Parrish, R. A. Calderone, and W. A. Fonzi, mBio 10:e00300-19, 2019, https://doi.org/10.1128/mBio.00300-19) take the next steps in understanding mitochondrial function by identifying proteins that are unique to a smaller phylogenetic group of microbes. Using the combination of in silico, biochemical, and microbiological assays, Sun and colleagues identified seven genes that are unique to the CTG fungal clade, which contains multiple important human pathogens, including Candida albicans, and showed that they are required for full ETC function during respiratory metabolism. Because respiratory metabolism is critical for fungal pathogenesis, these clade-specific mitochondrial factors may represent novel therapeutic targets.